Systems approach and modeling for sustainable groundwater irrigation: a case study in Mardin Kızıltepe plain - Mirhanoğlu, Adnan. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2018., 2018)
The use of water for agriculture has become one of the most important environmental issues since water resources are depleting very fast. Groundwater irrigation, therefore, is mostly the only alternative to sustain agricultural activities in arid and semi-arid places. The hydrology of groundwater resources and the impact of human activities that cause groundwater exploitation are complex, and this complexity causes strategic management problems. This study examines the impact of different groundwater management options for the long-term sustainable agriculture in the Kızıltepe Plain located in south-east of Turkey where groundwater is used with insufficient coordination and regulation. There has been a tremendous increase in number of wells and amount of irrigated land in Kızıltepe Plain particularly in the past ten years. This increase ultimately causes irreversible damage to groundwater resources and also triggers ecological destruction, which may occur in the future. System dynamics provides us tools to explore the relationship between nature and humans in a holistic way. Therefore, in this research, a dynamic simulation model is developed to understand the groundwater problem in a holistic way and also to seek sustainable groundwater irrigation management in Kızıltepe Plain. The dynamic model consists of four sectors representing groundwater resources, water extraction, land use change and crop profitability. The model is validated first structurally with different extreme condition tests and parameter sensitivity tests. Then, behavioral validation is performed by available data between 2005 and 2015. It is argued that although overexploitation of groundwater beyond its replenishment rates may be profitable for the farmers in the short term, it may cause irreversible economic and ecological damage in the long term. Scenario analyses performed reveal that state incentives for irrigated land and increases in irrigated crop price may cause an enormous increase in irrigated land. This increase may lead to excessive use of groundwater which may result in significant water scarcity for future generations. However, changing irrigation type from flood irrigation to drip irrigation may reduce the use of groundwater and help to achieve long term sustainable groundwater use in Kızıltepe Plain.
Keywords: Irrigation -- Mardin -- Kızıltepe.; Groundwater -- Mardin -- Kızıltepe.